I Can't, But We Can: Pendekatan Hipnoterapi untuk Meningkatkan Ketahanan Mental Pekerja dalam Situasi Darurat - Anwar, Syahferi; Ismayadi, Ismayadi; Damanik, Balqis Nurmauli; Asminanda, Cut Roza (Universitas, 2025)
The community service project aimed to enhance the mental resilience of workers facing emergency situations through a participatory hypnotherapy intervention conducted on October 22, 2024, at an outdoor hotel in North Sumatra. The project integrated orientation sessions, group hypnotherapy, and reflective discussions without formal measurement instruments, resulting in qualitative data that revealed significant improvements in relaxation, self-awareness, anxiety reduction, and social support. These findings not only confirm the effectiveness of hypnotherapy in managing work-related stress but also hold promise for advancing educational practices by incorporating stress management strategies into academic curricula and training programs. Keywords: Hypnotherapy, Mental Resilience, Work Stress, Education, Community Service